Uji Validitas dan Reabilitas Kuesioner Naranjo untuk Mengukur Adverse Drug Reactions (ADRs)Pasien Aterosklerosis - I Nengah Satria Wirananda; Fitri Apriliany; Novitarini (Universitas Bumigora, 2026)
Patients with atherosclerosis receive concomitant cardiovascular medications, and the use of multiple medications can increase the risk of adverse drug reactions (ADRs). ADRs assessment is crucial to differentiate drug side effects from other conditions, like comorbidities, drug interactions, or environmental factors. ADRs are generally measured using the Naranjo algorithm questionnaire. The purpose of this study is to determine the validity and reliability of the Naranjo questionnaire for measuring ADRs in patients with atherosclerosis. This study used a non-experimental, descriptive-analytical design with a cross-sectional approach and prospective observation. The subjects in this study were 30 patients with atherosclerosis, and data were collected using the Naranjo algorithm questionnaire. The results showed that the Naranjo algorithm questionnaire was valid, as the content validity test yielded a Pearson Correlation coefficient of >0.361. This instrument was deemed reliable because its Cronbach’s alpha was>0.60. Therefore, the Indonesian version of the Naranjo algorithm questionnaire is valid and reliable, and can be used to measure adverse drug reactions in patients with atherosclerosis.